INDUCTION OF NORMOCYTIC-NORMOCHROMIC ANAEMIA IN Clarias gariepinus (Burchell, 1822) EXPOSED TO ACUTE CONCENTRATION OF 1, 1-dimethyl 4,4-bipiridillium (PARAQUAT) UNDER LABORATORY CONDITIONS (FULafia Journal of Science and Technology, 2023)
fish were exposed to test water separately diluted with acute concentrations of paraquat of 0, 15, 20, 25 and 30mg/L. A 96Hrs exposure to acute concentrations of the toxicant resulted in normocytic-normochromic anaemia in the exposed fish. Blood indices attributable to normocytic-normochromic anaemia was observed with a significant (p0.05). White blood cells, lymphocytes, monocytes, Neutrophils, eosinophil and basophil were also not significantly different (p>0.05) with increasing concentrations of the toxicant